2020
DOI: 10.31014/aior.1992.03.01.197
|View full text |Cite
|
Sign up to set email alerts
|

Determinant Return on Assets and Its Impact on Assets Growth (Case Study of Sharia General Banks in Indonesia)

Abstract: This study aims to examine and analyze the determinants that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…So it can be concluded that intellectual capital has a positive effect on financial performance (ROA). The results of this study support stakeholder theory and resource theory, and are in line withHadiwijaya & Rohman (2013), Kurniasih & Heliantono (2016),Salim & Djausin (2019),Salim & Winanto (2020),Soewarno & Ramadhan (2020) andSuroso et al . (2017) who found that intellectual capital has a positive and significant effect on the company's financial performance.…”
supporting
confidence: 90%
“…So it can be concluded that intellectual capital has a positive effect on financial performance (ROA). The results of this study support stakeholder theory and resource theory, and are in line withHadiwijaya & Rohman (2013), Kurniasih & Heliantono (2016),Salim & Djausin (2019),Salim & Winanto (2020),Soewarno & Ramadhan (2020) andSuroso et al . (2017) who found that intellectual capital has a positive and significant effect on the company's financial performance.…”
supporting
confidence: 90%